Microstructure and wear behavior of in-situ hypereutectic Al–high Si alloys produced by selective laser melting. (5th June 2016) - Kang, Nan; Coddet, Pierre; Chen, Chaoyue; Wang, Yan; Liao, Hanlin; Coddet, Christian
Abstract: In this study, almost dense hypereutectic Al-50 Si alloys were fabricated in situ by selective laser melting (SLM) from the mixture of Al and Si powders under argon atmosphere. The effects of laser power on the microstructure and mechanical properties were determined regarding the size and morphology of primary Si phase (proeutectic Si). The phase analysis shows that the main phase of SLM-processed Al-Si alloys consists of Al and Si for all samples. Additionally, due to the vaporization behavior of Al, the Si content increases after melting process. The primary Si phase presents a smaller size (about 5 μm) than that in the conventional produced hypereutectic Al-Si alloys. Moreover, while the laser power increases, the spherical morphology of primary silicon turns into irregular shape. Besides, the maximum value of microhardness (188 Hv) was detected for the samples obtained at laser power of 320 W. The sample obtained at laser power of 350 W shows the lowest wear rate (5.5 × 10 − 4  mm 3  N − 1  m − 1 ). Graphical abstract: Highlights: Ultrafine microstructural dense hypereutectic Al-high Si alloys were fabricated by selective laser melting (SLM). The vaporization of Al can be observed for the sample obtained at high laser power. The size of primary silicon phase increases while the laser power increases. The SLM processed sample with higher silicon content and suitable size of primary silicon shows a higher wear resistance. SLM processed Al-high Si alloys are potential candidates for next generation electronic packaging material.